Outcomes of Left Main Percutaneous Coronary Intervention - aleem Ullah, Samiullah, Muhammad Abbas Khan, Javed Khurshed Shaikh, Gulzar Ali Buriro, Syed Nadeem Hassan Rizvi (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The objective of this research is to assess the efficacy of left main coronary artery (LMCA) revascularization and to document the outcomes for patients who underwent this procedure. Methodology: The National Institute of Cardiovascular Diseases (NICVD) in Karachi conducted a cross-sectional study from January 2018 to December 2019 and discovered that participants had a decreased risk of developing heart disease. All patients aged 18 and above who received percutaneous LMCA revascularization at the study location were considered for inclusion. We evaluated patient outcomes in the hospital by charting and doing telephonic follow-ups for one year. Regarding quantitative variables, the results were expressed as means and standard deviations, and concerning qualitative variables, as percentages. Results: The study center treated 95 patients with LM PCI during the study period. 68 (71.5%) of the people who had LM PCI had unprotected LM. LM PCI was most commonly performed on 44 patients (46.3%) presenting with unstable angina. Ninety-one (95.7%) patients required PCI due to native LM illness, while four patients (4.2%) underwent LM PCI as a rescue treatment. There were 41.7 ± 26.9 months of follow-up on average. Participants were followed up on average for 41.7 ±26.9 months, and they were admitted to the hospital on average for 4.45 ±3.2 days. The death rate in the hospital was 12.6%, and this was followed by the mortality rate at 1 year and a mean follow-up of 7.5% and 6.7%, respectively. Conclusion: Hemodynamically unstable patients, or those who cannot have bypass surgery for various reasons, have a successful therapy option in Pakistan: LM percutaneous coronary intervention. It may be necessary for the future to conduct prospective studies to evaluate whether PCI can be used to treat LM lesions when compared with existing treatments.